The importance of education in patients with metabolic syndrome with regard to their knowledge and attitudes about the disease, and the impact of education on laboratory parameters - Azra Bureković; Elvira Đozo; Anida Divanović (Medicinski glasnik, 2020)
Aim: A metabolic syndrome (MetS) increases the risk of heart disease and diabetes mellitus type 2, thus the aim of this study is to correlate the clinical and laboratory parameters in patients suffering from MetS who have previously had education compared to patients who have not had any education about a healthy lifestyle, and to check their knowledge and attitudes about healthy lifestyle. Methods: The study included patients of both genders aged 18 - 70 years, diagnosed with MetS, who are members of the Association of Diabetics in Canton of Sarajevo. It used anthropometric parameters, laboratory findings, and an original, structured questionnaire about diet and frequency of physical activities. Results: Clinical and laboratory parameters did not differ significantly between educated and uneducated patients, as well as habits in diet, physical activity, and knowledge about metabolic syndrome. The questions from the questionnaire have shown a good value of variance, suggesting that the questionnaire can be considered reliable. Conclusion: This study showed that people with metabolic syndrome are not educated and motivated enough to change their lifestyle. The need for education of such patients is necessary.
Keywords: cardiovascular disease; dyslipidemia; type 2 diabetes mellitus